2015
DOI: 10.1016/j.marenvres.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Home advantage? Decomposition across the freshwater-estuarine transition zone varies with litter origin and local salinity

Abstract: Expected increases in the frequency and intensity of storm surges and river flooding may greatly affect the relative salinity of estuarine environments over the coming decades. In this experiment we used detritus from three contrasting environments (marine Fucus vesiculosus; estuarine Spartina anglica; terrestrial Quercus robur) to test the prediction that the decomposition of the different types of litter would be highest in the environment with which they are associated. Patterns of decomposition broadly fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Similar comparisons in the literature were, in aggregate, not conclusive. Bierschenk et al (2012) found higher rates of cotton strip decomposition in streams than in marine sites, whereas Feio et al (2021) found highest decomposition rates of natural leaf litter in estuarine zones than in headwater streams, and Franzitta et al (2015) showed contrasting patterns of decomposition rates among three plant species along a salinity gradient from freshwater to saline water.…”
Section: Discussionmentioning
confidence: 94%
“…Similar comparisons in the literature were, in aggregate, not conclusive. Bierschenk et al (2012) found higher rates of cotton strip decomposition in streams than in marine sites, whereas Feio et al (2021) found highest decomposition rates of natural leaf litter in estuarine zones than in headwater streams, and Franzitta et al (2015) showed contrasting patterns of decomposition rates among three plant species along a salinity gradient from freshwater to saline water.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, when comparing the decomposition rates of Phragmites australis and Fucus vesiculosus, only the macrophyte P. australis decomposed significantly faster in the place where they occur naturally, providing evidence for an HFA effect for P. australis (Lopes et al, 2013). Franzitta et al (2015) demonstrated HFA for detritus decomposition along estuarine gradients. The decomposition rates of Quercus in 'freshwater' and Fucus in 'high salinity' conditions showed that more rapid decomposition rates occurred at their 'home' habitats, which corroborated the occurrence of HFA in aquatic ecosystems.…”
Section: Decomposition Rate and Hfamentioning
confidence: 99%
“…Presently, there is no overwhelming evidence to suggest that HFA occurs commonly and consistently in terrestrial and aquatic decomposition. Some studies have provided evidence to support HFA effects in decomposer communities of terrestrial ecosystems (Ayres et al, 2009;Veen et al, 2015a;Li et al, 2017) and aquatic ecosystems (Jackrel and Wootton, 2014;Franzitta et al, 2015;Leroy et al, 2017). By contrast, several studies have found no support for this phenomenon either in terrestrial ecosystems (Gieβelmann et al, 2011;Veen et al, 2015b) or aquatic ecosystems (Fenoy et al, 2016), or have reported variable results (Chomel et al, 2015;Jewell et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth testing further whether the specialisation of freshwater microbes on locally derived litter is widespread (see Franzitta et al, 2015;Leroy et al, 2017;Xie, Xie, Xiao, Chen, & Li, 2017), and temporally variable. If so, litter-decomposer interactions will be more dynamic than has been recognised, and so could be more easily altered by the intensifying impacts of global environmental change (including range shifts of species and genotypes/populations) and human impacts on riparian vegetation and freshwater decomposer communities (Ferreira et al, 2016;Kominoski & Rosemond, 2011;Kominoski et al, 2013).…”
Section: Con Clus Ionmentioning
confidence: 99%